Meriones unguiculatus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
154. Mongolian Jird Meriones unguiculatus French: Mérione de Mongolie / German: Mongolische Rennratte / Spanish: Gerbillo de Mongolia Other common names: Clawed Jird, Mongolian Gerbil Taxonomy. Gerbillus unguiculatus Milne-Edwards, 1867, Eul-che-san hao (= Ershi san hao), 16 km north-east of Tschang- Kur, northern Shanxi, China. Initially considered a member of genus Ger- billus, M. unguiculatus was them removed to Pallasiomys and later attributed to Meriones. It was reviewed by G. M. Allen in 1940, G. B. Corbet in 1978, and I. Ya. Pavlinov and colleagues in 1990 on basis of morphological traits. Some authors described also a peculiar phallic morphology and contrasted it with M. meridianus and Rhombomys opimus. R. Gamperl and G. Vistorin in 1984 provided the most detailed karyotype for this species and its variability. Molecular analysis by M. Ito and team in 2010 found M. unguiculatus to be a monophyletic clade and sister to M. meridianus. Monotypic. Distribution. Russia (SE Siberia, including ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 648, DOI: 10.5281/zenodo.6887260 ...